2007
DOI: 10.1002/ange.200604335
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische carbophile Aktivierung: Platin‐ und Gold‐π‐Säuren als Katalysatoren

Abstract: Platin‐ und Goldkatalysatoren gewinnen aufgrund ihrer hohen Effizienz und erstaunlichen Vielfalt für atomökonomische Umsetzungen rasch an Bedeutung. Dabei erlaubt es die Korrelation zwischen ihrem chemischen Verhalten und den vorhandenen Strukturdaten, der bekannten Koordinationschemie und den auf relativistischen Effekten beruhenden Besonderheiten ihrer metallorganischen Derivate, grundlegende Prinzipien der katalytischen carbophilen Aktivierung durch π‐Säuren zu formulieren. Platin‐ und Goldkomplexe sind kei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
173
0
29

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 941 publications
(205 citation statements)
references
References 554 publications
(194 reference statements)
3
173
0
29
Order By: Relevance
“…Ermutigt [16] (Wasserstoffatome sind nicht gezeigt; Ellipsoide markieren 50 % Aufenthaltswahrscheinlichkeit. )…”
Section: Methodsunclassified
“…Ermutigt [16] (Wasserstoffatome sind nicht gezeigt; Ellipsoide markieren 50 % Aufenthaltswahrscheinlichkeit. )…”
Section: Methodsunclassified
“…[6,7] In the presence of gold catalysts, it has been well-established that common 2-oxo-1-alkynebenzenes generate gold-benzopyrilium (I) or carbenoid carbonyl ylides (II) with a variety of dipolarophiles through a distinct [4+2] or [3+2] cycloaddition to obtain diverse carbocycles or oxacycles (Scheme 1). [8,9] Although various goldcatalyzed reactions with 2-oxo-1-alkynebenzene substrates have been reported, most of these transformations have only focused on enynals.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that ethyl, methyl, tert-butyl, benzyl, and allyl acetoacetates (1 a-e) all reacted with 2 a to afford the furans 3 a-e in 55-66 % yields ( Table 2, entries [1][2][3][4][5]. The sterically more hindered 1 f also smoothly underwent the domino reaction (Table 2, entry 6).…”
mentioning
confidence: 98%
“…[1] However, the exposure of the C3-unsubstituted furan 11 and 2 a to the standard reaction conditions failed to deliver any 3 a [Eq. (2)], thus suggesting that the protodeauration of the gold 3-furyl complex could not be involved in this cascade process.…”
mentioning
confidence: 99%
See 1 more Smart Citation